2020
DOI: 10.2967/jnumed.120.242347
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging of Very Late Antigen-4 in Acute Lung Injury

Abstract: Inflammation plays a central role in the pathogenesis of acute lung injury (ALI) during both the acute pneumonitis stage and progression into the chronic fibroproliferative phase, leading to pulmonary fibrosis. Currently, there is an unmet clinical and research need for noninvasive ways to monitor lung inflammation through targeting of immunoregulatory pathways contributing to ALI pathogenesis. In this study, we evaluated the role of targeted imaging of very late antigen-4 (VLA-4), as a key integrin mediating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Additionally, we have recently reported that [ 64 Cu]NODAGA-CG34, a PET tracer that selectively binds to chemokine-like receptor-1 (CMKLR1), detects the accumulation of monocyte-derived macrophages in the lungs of mice with ALI [ 62 ]. Other emerging molecular imaging targets include, α 4 β 1 integrin [ 63 ], leukocyte receptor CD11b [ 64 ], folate receptor-β [ 65 ], and translocator protein receptor [ 66 ], which have been successfully used for noninvasive detection of lung inflammation in ALI.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we have recently reported that [ 64 Cu]NODAGA-CG34, a PET tracer that selectively binds to chemokine-like receptor-1 (CMKLR1), detects the accumulation of monocyte-derived macrophages in the lungs of mice with ALI [ 62 ]. Other emerging molecular imaging targets include, α 4 β 1 integrin [ 63 ], leukocyte receptor CD11b [ 64 ], folate receptor-β [ 65 ], and translocator protein receptor [ 66 ], which have been successfully used for noninvasive detection of lung inflammation in ALI.…”
Section: Discussionmentioning
confidence: 99%
“…Combining the above results and the reported conclusions, we believe that [ 18 F]FBTA represents a manifest improvement over [ 18 F]FDG in imaging lung in ammation. 67 Ga/ 68 Ga-citrate 20,21 , 64 Cu-αCD11b 22 , 64 Cu-DOTA-ECL1i 23 and 64 Cu-LLP2A 24 can target speci c receptors or proteins of immune cells and dynamically re ect the spatial distribution of immune cellmediated in ammation in ALI. However, the high uptake in organs or tissues of no interest and poor metabolic kinetics of these tracers affect the judgment of lung injury lesions [20][21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…67 Ga/ 68 Ga-citrate 20,21 , 64 Cu-αCD11b 22 , 64 Cu-DOTA-ECL1i 23 and 64 Cu-LLP2A 24 can target speci c receptors or proteins of immune cells and dynamically re ect the spatial distribution of immune cellmediated in ammation in ALI. However, the high uptake in organs or tissues of no interest and poor metabolic kinetics of these tracers affect the judgment of lung injury lesions [20][21][22][23][24] . Here, we compare in detail the differences in imaging parameters and distributions between the above tracers and [ 18 F]FBTA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations